2001
DOI: 10.1145/383738.383742
|View full text |Cite
|
Sign up to set email alerts
|

An automatic continuation strategy for the solution of singularly perturbed nonlinear boundary value problems

Abstract: In a recent paper, the present authors derived an automatic continuation algorithm for the solution of linear singular perturbation problems. The algorithm was incorporated into two general-purpose codes for solving boundary value problems, and it was shown to deal effectively with a large test set of linear problems. The present paper describes how the conintuation algorithm for linear problems can be extended to deal with the nonlinear case. The results of exstensive numerical testing on a set of nonlinear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…There is only a compound tolerance parameter for code ACDC, [44] which has been varied between 10 À6 and 10 À8 , and numerical results agree to 8 decimal places.…”
Section: Reaction Name Chemical Equationmentioning
confidence: 83%
“…There is only a compound tolerance parameter for code ACDC, [44] which has been varied between 10 À6 and 10 À8 , and numerical results agree to 8 decimal places.…”
Section: Reaction Name Chemical Equationmentioning
confidence: 83%
“…This leads to extreme numerical sensitivity [36] of the 2PBVP needed for solution by the method of characteristics. Only rather recently a suitable method [37] could be found to solve them.…”
Section: Numerical Computation Of Generating Functions (Gf) Of Polymementioning
confidence: 99%
“…Only recently (Costa and Dias, 2003) could a solution be found, thanks to the use of the integrator in automatic continuation code ACDC (Cash et al, 1995(Cash et al, , 2001Bashir-Ali et al, 1998).…”
Section: Mass Balance Equationsmentioning
confidence: 99%
“…Code ACDC (Cash et al, 2001) can deal with the "stiff" systems (Hairer and Wanner, 2002) found in free-radical polymerisation (discussed in next section) and this is a relatively easy problem for that method. Prediction of weight-average molecular weight takes about 30 s CPU before gelation, and each prediction of sol fraction and M w after gelation takes about 59 s. Computations were performed with a PIV 1.5 GHz running Linux (computing times are about the same with a dual G4 Power PC running Apple MacOSX, also with a program compiled with GNU C compiler gcc-2.95 and associated Fortran compiler).…”
Section: Numerical Treatment Of Non-radical Polymerisation Modelsmentioning
confidence: 99%